Immunomodulatory Role of Urolithin A on Metabolic Diseases - Toney, Ashley Mulcahy (Biomedicines, 2021)
Urolithin A (UroA) is a gut metabolite produced from ellagic acid-containing foods such as pomegranates, berries, and walnuts. UroA is of growing interest due to its therapeutic potential for various metabolic diseases based on immunomodulatory properties. Recent advances in UroA research suggest that UroA administration attenuates inflammation in various tissues, including the brain, adipose, heart, and liver tissues, leading to the potential delay or prevention of the onset of Alzheimer’s disease, type 2 diabetes mellitus, and non-alcoholic fatty liver disease. In this review, we focus on recent updates of the anti-inflammatory function of UroA and summarize the potential mechanisms by which UroA may help attenuate the onset of diseases in a tissue-specific manner. Therefore, this review aims to shed new insights into UroA as a potent anti-inflammatory molecule to prevent immunometabolic diseases, either by dietary intervention with ellagic acid-rich food or by UroA administration as a new pharmaceutical drug.